Identifying Early Infections in the Setting of CRS With Routine and Exploratory Serum Proteomics and the HT10 Score Following CD19 CAR-T for Relapsed/Refractory B-NHL. Issue 4 (5th April 2023) - Rejeski, Kai; Blumenberg, Viktoria; Iacoboni, Gloria; Lopez-Corral, Lucia; Kharboutli, Soraya; Hernani, Rafael; Petrera, Agnese; Müller, Niklas; Hildebrand, Friederike; Frölich, Lisa; Karschnia, Philipp; Schmidt, Christian; et al.
Abstract : Early fever after chimeric antigen receptor T-cell (CAR-T) therapy can reflect both an infection or cytokine release syndrome (CRS). Identifying early infections in the setting of CRS and neutropenia represents an unresolved clinical challenge. In this retrospective observational analysis, early fever events (day 0–30) were characterized as infection versus CRS in 62 patients treated with standard-of-care CD19.CAR-T for relapsed/refractory B-cell non-Hodgkin lymphoma. Routine serum inflammatory markers (C-reactive protein [CRP], interleukin-6 [IL-6], procalcitonin [PCT]) were recorded daily. Exploratory plasma proteomics were performed longitudinally in 52 patients using a multiplex proximity extension assay (Olink proteomics). Compared with the CRS only cohort, we noted increased event-day IL-6 (median 2243 versus 64 pg/mL, P = 0.03) and particularly high PCT levels (median 1.6 versus 0.3 µg/L, P < 0.0001) in the patients that developed severe infections. For PCT, an optimal discriminatory threshold of 1.5 µg/L was established (area under the receiver operating characteristic curve [AUCROC ] = 0.78). Next, we incorporated day-of-fever PCT levels with the patient-individual CAR-HEMATOTOX score. In a multicenter validation cohort (n = 125), we confirmed the discriminatory capacity of this so-called HT10 score for early infections at first fever (AUCROC = 0.87, P < 0.0001, sens. 86%, spec. 86%). Additionally, Olink proteomics revealed pronounced immune dysregulation and endothelial dysfunction in patients with severe infections as evidenced by an increased ANGPT2/1 ratio and an altered CD40/CD40L-axis. In conclusion, the high discriminatory capacity of the HT10 score for infections highlights the advantage of dynamic risk assessment and supports the incorporation of PCT into routine inflammatory panels. Candidate markers from Olink proteomics may further refine risk-stratification. If validated prospectively, the score will enable risk-adapted decisions on antibiotic use. Abstract :